2013
DOI: 10.1108/13673271311300822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing seeming incompatibilities to foster knowledge creation and innovation

Abstract: PurposeThe purpose of this paper is to provide an example of how an apparently incongruent combination of organizational variables can have a positive effect on innovation through knowledge creation.Design/methodology/approachBased on previous theory, four original hypotheses were developed and later tested with empirical data collected from 125 research and development organizations in Japan, using analysis of variance and regression analysis.FindingsManagerial influences and resources can significantly inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 69 publications
0
24
0
2
Order By: Relevance
“…The literature on knowledge creation and absorptive capacity reveals mixed results. On one hand, some studies show that new knowledge creation can be an outcome of the firm's absorptive capacity (Chou, ; Matusik, ; Sun, ), because absorptive capacity acts as an accelerator of new knowledge creation (Zelaya‐Zamora and Senoo, ). On the other hand, some authors found that both can create a synergistic effect, reinforcing each other and supporting innovation (Su et al, ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The literature on knowledge creation and absorptive capacity reveals mixed results. On one hand, some studies show that new knowledge creation can be an outcome of the firm's absorptive capacity (Chou, ; Matusik, ; Sun, ), because absorptive capacity acts as an accelerator of new knowledge creation (Zelaya‐Zamora and Senoo, ). On the other hand, some authors found that both can create a synergistic effect, reinforcing each other and supporting innovation (Su et al, ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Lin [22] used the theory of innovation diffusion to empirically study the impact of three context variables (organizational readiness, expected benefits, and organizational learning capabilities), which can reflect that they can have an effect on the applicability of knowledge management systems. Zelaya-Zamora [23] argued that management influences and resources can interact significantly. They then have an impact on an organization's knowledge creation capabilities, which in turn are positively correlated with the organization's innovation performance.…”
Section: The Basis Of Research Of Knowledge Innovation System In Entementioning
confidence: 99%
“…All successful organizations create and use knowledge as a fundamental tool for interacting with their environments, absorbing information, making informed decisions, and carrying out actions based on the combination of this knowledge and organizational experiences, values, and rules [1,12,17]. All of these are activities that make up the knowledge generation process in organizations [18].…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…The challenge is to build systems that collect the learning processes acquired during projects and ongoing activities, capture that knowledge in a database or document, and spread it throughout the entire organization [8,9]; and that will be useful for innovation strategies. In this sense, there are many studies discussing how knowledge generation is positively related to innovation and performance [10][11][12]; but the impact of individual skills and organizational factors to generate knowledge is still unexplored [7,13].…”
Section: Introductionmentioning
confidence: 99%